Encoding of Rules by Neurons in the Human Dorsolateral Prefrontal Cortex. (21st November 2012) - Mian, Matthew K.; Sheth, Sameer A.; Patel, Shaun R.; Spiliopoulos, Konstantinos; Eskandar, Emad N.; Williams, Ziv M.
Abstract : We use rules to extend learned behavior beyond specific instances to general scenarios. The prefrontal cortex (PFC) is thought to play an important role in representing rules, as evidenced by subjects who have difficulty in following rules after PFC damage and by animal studies demonstrating rule sensitivity of individual PFC neurons. How rules are instantiated at the single-neuronal level in the human brain, however, remains unclear. Here, we recorded from individual neurons in the human dorsolateral prefrontal cortex (DLPFC) as subjects performed a task in which they evaluated pairs of images using either of 2 abstract rules. We find that DLPFC neurons selectively encoded these rules while carrying little information about the subjects' responses or the sensory cues used to guide their decisions.